OPTIMIZATION OF THE CASTINGS PRODUCTION TECHNOLOGY USING SUPERCOMPUTER SKIP - A. N. Chichko; S. G. Likhouzov; T. V. Matjushinets; V. F. Sobolev; O. I. Chichko (Литьë и металлургия)
One of the variants of optimization of the castings production technologies with the help of multiple-processor technologies of supercomputer SKIF is presented.